The effects of traumatic brain Injury, post-traumatic stress disorder on Amyloid-β associated network hyperconnectivity and progression of gray matter atrophy - Susanne G. Mueller (NeuroImage: Clinical)
Background: Amyloid-β associated network hypersynchrony is an early manifestation of pre-clinical Alzheimer’s Disease (AD). The overall goal was to investigate a. how TBI and PTSD influence hypersynchrony expression and b. how progressing gray matter atrophy affects hypersynchrony expression. Methods: T1-weighted images, resting-state fMRIs and amyloid-β SUVRs were obtained from 234 DoD-ADNI subjects with or without TBI and/or PTSD. The denoised BOLD signal from 382 rois was extracted with CONN and dynamic resting state analysis was used to identify 8 states including one corresponding to a hypersynchrony state (HSS). SuStaIn with gray matter volumes and amyloid-β SUVR as inputs was used to identify 2 subtypes with progressive gray matter loss. Results: HSS dwell-time correlated positively with amyloid-β (Kendall tau = 0.125,p = 0.047) and tau Braak stage 5&6 SUVR (Kendall tau = 0.200,p = 0.035). TBI increased the likelihood to observe the HSS (81 % with vs. 18 % wo TBI p < 0.001) as did a diagnosis of PTSD (67.4 % with vs. 32.6 % wo PTSD, p = 0.003). The SuStaIn subtypes differed mostly by the timing of the amyloid-β build-up but not by atrophy pattern. Subtype 2 had higher amyloid-β loads and longer HSS dwell-times than subtype 1 that had higher CAPS scores than subtype 2. Gray matter atrophy did not influence HSS dwell-time. Conclusion: TBI and PTSD increased the likelihood to observe HSS. HSS dwell time was determined by AD pathology severity. The subtype characteristics indicate that PTSD drives gray matter loss in subtype 1 and AD pathology that in subtype 2. Severity of gray matter atrophy influenced neither HSS occurrence nor intensity.